PENGARUH KEHARMONISAN KELUARGA DAN LINGKUNGAN SOSIAL SEKOLAH TERHADAP VANDALISME REMAJA SMP NEGERI 14 PONTIANAK - Muliyani Muliyani; Yohanes Bahari; Rustiyarso Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the interaction of family and social environment on thevandalism behavior of eighth grade students of SMP Negeri 14 Pontianak. Thisresearch method is quantitative with a research sample of 110 VIII students usingpurposive sampling. Data was taken using a questionnaire. The results showed thatvandalism was low at 60.8%, family harmony was 44.7% and the school environmentwas categorized as very high at 34.4%. The results of the test show Fcount (31,328) >Ftable (3.08) and a significance of 0.00 < 0.05, meaning that family harmony and socialenvironment have a significant effect on vandalism behavior. tcount of the decent familyharmony variable -4.486 > ttable 1.982 with a significance of 0.00 <0.05, which meansthat there is a significant negative effect. tcount of the appropriate school socialenvironment variable -2.547 > ttable 1.982 with a significance of 0.01 <0.05, whichmeans that there is a significant negative effect. Regression equation Y'= 68.074+ (-0.418) + (-0.313) + e. The determinant value of Adjusted R2 = 0.358, which means thatthe influence of family interaction and social environment on vandalism behavior is low,namely 35.8%.Keywords: Harmonious family, School Social Environment, Vandalism.